2020
DOI: 10.1101/2020.04.03.023036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addition of Multiple Introns to a Cas9 Gene Results in Dramatic Improvement in Efficiency for Generation of Gene Knockouts in Plants

Abstract: Running title: High efficiency site-targeted mutagenesis with an intronized Cas9 gene AbstractThe recent discovery of the mode of action of the CRISPR/Cas9 system has provided biologists with a useful tool for generating site-specific mutations in genes of interest. In plants, site-targeted mutations are usually obtained by stably transforming a Cas9 expression construct into the plant genome. The efficiency with which mutations are obtained in genes of interest can vary considerably depending on specific feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…While we have shifted the distribution to 4-to 6-plex mutants, even higher levels will be needed to rapidly mutate genomes and large gene families. It would be interesting to combine the RPS5A::BP-BP vector with different strategies to express gRNAs and/or by including introns in the Cas9-coding sequence (Gr€ utzner et al, 2020). Experimenting with the different gRNA expression strategies would be especially interesting, given that the gRNAs are the limiting factor in the RPS5A::BP-BP vector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we have shifted the distribution to 4-to 6-plex mutants, even higher levels will be needed to rapidly mutate genomes and large gene families. It would be interesting to combine the RPS5A::BP-BP vector with different strategies to express gRNAs and/or by including introns in the Cas9-coding sequence (Gr€ utzner et al, 2020). Experimenting with the different gRNA expression strategies would be especially interesting, given that the gRNAs are the limiting factor in the RPS5A::BP-BP vector.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the removal of the C‐terminal NLP NLS from the SV40‐NLP configuration reduced mutagenesis below the background level of the assay (Osakabe et al., 2016). It was shown that an SV40 NLS on both ends of a Cas9 containing 13 introns compared to a single C‐terminal SV40 NLS increased the number of T1 plants with a KO phenotype from 58 to 72% (Grützner et al., 2020). In wheat and maize protoplasts, the double‐BP architecture improved the Cas9 and Cas12a adenine base editor (ABE) editing rates compared to a C‐terminal triple SV40 NLS (Gaillochet et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While we have shifted the distribution to 4-6-plex mutants, even higher levels will be needed to rapidly mutate genomes and large gene families. It would be interesting to combine the RPS5A::BP-BP vector with different strategies to express gRNAs and/or by including introns in the Cas9 coding sequencing 32 . Experimenting with the different gRNA expression strategies would be especially interesting given that the gRNAs are the limiting factor in the RPS5A::BP-BP vector.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the removal of the C-terminal NLP NLS from the SV40-NLP configuration reduced mutagenesis below the background level of the assay 31 . It was shown that an SV40 NLS on both ends of a Cas9 containing 13 introns, instead of a single C-terminal SV40 NLS, increased the number of T1 plants with a KO phenotype from 58% to 72% 32 . In wheat and maize protoplasts, the double-BP architecture improved Cas9 and Cas12a adenine base editor (ABE) editing rates compared to a C-terminal triple SV40 NLS 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of 5'UTR intron mediated expression improvements have led to inclusion of 5'UTR intron in many transgenes' designs (11). Benefits from adding multiple introns into transgenes are however controversial, while some studies describe benefits achieved with constructs containing multiple endogenous introns (12) and heterologous introns (13)(14)(15) other studies report no added benefit achieved by more than a single intron (16).…”
Section: Introductionmentioning
confidence: 99%